2015
DOI: 10.18814/epiiugs/2015/v38i3/001
|View full text |Cite
|
Sign up to set email alerts
|

Improved Geochronologic Accuracy and Precision for the ICS Chronostratigraphic Charts: Examples from the late Cambrian–Early Ordovician

Abstract: The utility of ICS International Chronostratigraphic Charts (ICS Charts) relies on the accuracy and precision of reported geochronologic dates and their relationship to the bases of global chronostratigraphic units. However, an examination of some early Paleozoic dates (i.e., Cambrian-Ordovician boundary and lowest Ordovician) on the ICS Charts shows that they differ from originally reported and late recalculated dates. Thus, they record a numerical precision that differs from these revised dates. The dates as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Both the 2006 and 2008 reports do not illustrate the previously named, documented and strong HERB Event below the purported TOCE excursion. A re-evaluation of latest Cambrian geochronology (Landing et al 2015) suggests that the HERB Event and middle Saukiella junia Subzone is c. 2 Ma older than the correlation of TOCE by Peng & Babcock (2008).…”
Section: B the Ever-shifting Meaning Of Tocementioning
confidence: 79%
See 1 more Smart Citation
“…Both the 2006 and 2008 reports do not illustrate the previously named, documented and strong HERB Event below the purported TOCE excursion. A re-evaluation of latest Cambrian geochronology (Landing et al 2015) suggests that the HERB Event and middle Saukiella junia Subzone is c. 2 Ma older than the correlation of TOCE by Peng & Babcock (2008).…”
Section: B the Ever-shifting Meaning Of Tocementioning
confidence: 79%
“…1) credulously accepted existence of an uppermost Cambrian TOCE excursion based on the Zhu et al (2006) and Peng & Babcock (2008) papers, and illustrated both the documented HERB and asserted TOCE excursions; this meant there were two strong, global uppermost Cambrian negative excursions separated by c. 2 Ma ( Fig. 1; see refined chronology of Landing et al 2015). Because Zhu et al (2006) had shown the negative TOCE excursion at the 'Mass Extinction (Ptychaspid Biomere)', this was interpreted (by EL in Landing et al 2011) to mean that TOCE actually existed and should be positioned at the bases of the coterminant Cordylodus proavus Zone (conodonts) and Laurentian Eurekia apopsis Zone (trilobites).…”
Section: B the Ever-shifting Meaning Of Tocementioning
confidence: 91%
“…Similarly, Babcock and Peng's (2007, p. 65) "third Cambrian series will correspond roughly to the Middle Cambrian of some regional correlation schemes" and thus is similar to the regional Avalonian Middle Cambrian Subsystem (Cowie et al, 1972;Landing, 1998a, b) and corresponds precisely to the global Middle Cambrian Subsystem of Landing et al (2013aLanding et al ( , 2018. Finally, "the uppermost series (the Furongian Series) corresponds to the … [Upper Cambrian] as used in South China … and … Kazakhstan" (Peng and Babcock, 2007, p. 65) and to the proposed global Upper Cambrian Subsystem of Landing et al (2015Landing et al ( , 2018.…”
Section: History Of Proposalmentioning
confidence: 80%
“…The source of the 497 Ma date for the base of the Upper Cambrian Subsystem and Paibian Series (Peng and Babcock, 2008;Zhu et al, 2018) has long remained unknown, although it is repeated by Cohen et al (2013 and updates). The available evidence indicates the Middle-Upper Cambrian Subsystem boundary can only be bracketed by U-Pb zircon dates of 494.4 ± 3.5 Ma in theDrumian (Landing et al, 2015a) and 488.71 ± 1.17 Ma just below the proposed Lawsonian Stage (see Landing et al, 2010aLanding et al, , 2011Landing et al, , 2015.…”
Section: Upper Cambrian Subsystem and Late Cambrian Subperiodmentioning
confidence: 99%
“…The late Cambrian and earliest Ordovician have a paucity of radiometric dates 52 , and only two can be directly related to the available magnetostratigraphy ( Fig. 7a and Supplementary Table 4 ).…”
Section: Resultsmentioning
confidence: 99%